2021
DOI: 10.1080/21678421.2021.1936061
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retrovirus K (HERV-K) env in neuronal extracellular vesicles: a new biomarker of motor neuron disease

Abstract: Objective: Human endogenous retroviruses (HERVs) have been gradually confirmed to be involved in the onset and progression of motor neuron disease(MND). However, noninvasive detection of HERVs in the central nervous system is lacking. The aim of this study is to verify the relationship between the level of HERV-K env in neuronal extracellular vesicles in plasma and the onset and severity of MND. Methods: We extracted neuronal extracellular vesicles from plasma of 39 MND patients and 30 age-and sex-matched cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Although coronavirus can evade and inhibit the IFN response to achieve high pathogenicity [ 39 , 40 , 41 , 42 , 43 ], much evidence has shown that IFN-I and IFN-III still have the potential to treat SARS, MERS, and COVID-19 [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. As a HERV family closely related to the growth and development of the host, HERV-K is often related to the abnormal activation of diseases, and many biomarkers of disease take this as the development point [ 26 , 51 , 52 ]. In this study, we confirmed that the activation of HERV-K leads to the activation of the IFN pathway, which provides a new direction for the potential mechanism of interferon production; at the same time, it also provides a new view of the physiological function of HERV-K. We think that when disease occurs, HERV-K participates in the regulation of immunity and accelerates the recovery from disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although coronavirus can evade and inhibit the IFN response to achieve high pathogenicity [ 39 , 40 , 41 , 42 , 43 ], much evidence has shown that IFN-I and IFN-III still have the potential to treat SARS, MERS, and COVID-19 [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. As a HERV family closely related to the growth and development of the host, HERV-K is often related to the abnormal activation of diseases, and many biomarkers of disease take this as the development point [ 26 , 51 , 52 ]. In this study, we confirmed that the activation of HERV-K leads to the activation of the IFN pathway, which provides a new direction for the potential mechanism of interferon production; at the same time, it also provides a new view of the physiological function of HERV-K. We think that when disease occurs, HERV-K participates in the regulation of immunity and accelerates the recovery from disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transgenic mice that expressed the Env under a neuronal promoter developed an ALS-like syndrome with exclusive degeneration of the upper and lower motor neurons [22]. Other groups have reproduced the discovery of HERV-K activation in individuals with ALS [58,59] although the activation may not be specific for ALS [24,25]. HERV-K (HML-2) activation has also been seen in individuals with frontotemporal dementia [58] (Fig.…”
Section: Detection Of Reverse Transcriptase Activity In Alsmentioning
confidence: 99%
“…Since DNA is stable, it can be easily measured quantitatively by droplet digital PCR in serum, plasma or CSF but needs to be distinguished from chromosomal copies of the viral genes [120]. HML-2 Env protein can also be measured using immunoprecipitation or a sandwich ELISA [59]. Specific epitopes have been identified on the HML-2 Env protein to which ALS patients develop antibodies [62].…”
Section: Monitoring Of Hml-2 In Patients With Alsmentioning
confidence: 99%
“…High levels of expression of HML‐2 have been found in autopsied brain samples from subsets of individuals with ALS 12, 13 . In one study HML‐2 envelope (env) protein was detected in plasma‐derived extracellular vesicles with higher levels in advanced stages of the illness 14 . Expression of the env protein in neurons triggers neurodegeneration in vitro and motor neuron disease in a transgenic mouse model 12 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 In one study HML‐2 envelope (env) protein was detected in plasma‐derived extracellular vesicles with higher levels in advanced stages of the illness. 14 Expression of the env protein in neurons triggers neurodegeneration in vitro and motor neuron disease in a transgenic mouse model. 12 In an open label study, reduction of HML‐2 viral load in serum of individuals with ALS treated with anti‐retroviral therapy was associated with a slower clinical progression.…”
Section: Introductionmentioning
confidence: 99%